Talent identification of wrestling athletes using the analytic hierarchy process method approach - Fendi Ferdiana; Agus Rusdiana; Iman Imanudin; Badruzaman Badruzaman; Angga M. Syahid; Tono Haryono; Iwa Ikhwan Hidayat Iwa Ikhwan Hidayat (Universitas Sriwijaya, 2023)
The research aims to identify the talent of wrestlers aged 10 to 14 years. The data collected was analysed using the Analytic Hierarchy Process (AHP) with the Expert Choice v. 11 application to find out which elements play an important role in supporting wrestlers. Mixed-methods research (MMR) was used in this study with the study of literature and questionnaires through Google Forms to 25 trainers in Indonesia. The results of this study have three criteria and 15 sub-criteria. These criteria are anthropometry (33.1%), biomotority (33.3%) and somatotype (3.3%). As for the sub-criteria mesomorph (16.3%), endomorph (8.7%), ectomorph (8.3%)1, lung endurance (7.9%), agility (7.0%), speed (6.9%), strength (6.2%), IMT (6%), height (5.9%), flexibility (5.3%), weight (5.1%), body length (4.4%), arm length (4.0%), body fat (3.9%) and sitting height (3.8%). This talent identification model can determine the priority variable in the identification of the talent of a wrestler.